2020
DOI: 10.1007/s00161-020-00905-0
|View full text |Cite
|
Sign up to set email alerts
|

A peridynamic-based machine learning model for one-dimensional and two-dimensional structures

Abstract: With the rapid growth of available data and computing resources, using data-driven models is a potential approach in many scientific disciplines and engineering. However, for complex physical phenomena that have limited data, the data-driven models are lacking robustness and fail to provide good predictions. Theory-guided data science is the recent technology that can take advantage of both physics-driven and data-driven models. This study presents a novel peridynamics-based machine learning model for one-and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 62 publications
1
6
0
Order By: Relevance
“…  Moreover, it is observed that the obtained coefficients as given in Eq. (A1-A3) for the bondbased machine learning model in this study agree very well with those obtained in [54].…”
Section:  =supporting
confidence: 88%
See 3 more Smart Citations
“…  Moreover, it is observed that the obtained coefficients as given in Eq. (A1-A3) for the bondbased machine learning model in this study agree very well with those obtained in [54].…”
Section:  =supporting
confidence: 88%
“…As given in Section 4, the PD-based ML model is obtained for material points with their 112 surrounding material points. However, for material points that have less than 112 surrounding material points or some broken interactions such as material points near boundary surfaces or near crack surfaces, the developed ML models can produce significant errors [49]. On the other hand, generating training data for these special cases can be very timeconsuming.…”
Section: Fig 3 Procedures To Obtain Coefficients For the ML Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…FNN-based simulation has since been extended to capture more complex behaviours such as discrete dislocation 14 and fracture. 15 Recurrent neural networks (RNNs) advance FNNs by incorporating time sequence prediction capability and have shown excellent performance in modelling the behaviour of path-dependent materials. [16][17][18] Recently, more versatile data-driven modelling strategies have been tailored to enhance model interpretability and generalisation, such as data-driven multiscale modelling that considers the evolution of microstructural characteristics, [19][20][21][22][23] Bayesian theory based uncertainty modelling [24][25][26] and physicsinformed neural networks that enforce prior knowledge to the neural network as additional constraints for improving robustness.…”
Section: Introductionmentioning
confidence: 99%